Strategies For Sustaining Manufacturing Competitiveness: Comparative Case Studies In Australia And Sweden - Soosay, Claudine; Nunes, Breno; John Bennett, David; Sohal, Amrik; Juhaini, Jabar; Winroth, Mats (Emerald Group Publishing Limited, 2016)
The purpose of this paper is to report an investigation of local sustainable production in Australia and Sweden aimed at exploring the factors contributing to survival and competitiveness of manufacturing companies. Design/methodology/approach - In Australia, six companies were studied in 2010, with comparisons being made with three of them from earlier projects. In Sweden, eight manufacturing companies were studied on two occasions 30 years apart, in 1980 and 2010. To provide a valid comparative perspective a common format for data collection and analysis was used. Findings - There has been a shift in the nature of competition in both Sweden and Australia due to an increasing complexity of the global business environment as well as changes in technology and customer expectations. Despite the differences in country context, the findings suggest that all the manufacturing companies have a good awareness of the elements of the market environment and the relationships with their competitive strategy. However, in general, the Swedish companies have more experience of managing the risks and benefits from operating in the international environment. Research limitations/implications - The results of the research are based on a relatively small sample of case companies in a limited number of industrial sectors. There are methodology implications for future research in the area. Practical implications - The research results have practical implications for the manufacturing industry, especially for companies operating in a competitive international environment. Originality/value - The paper is based on original case research and comparative analysis of data from different geographical contexts. It contributes to both theory and management practice about the strategic resources, decision choices, competitive environments and firm values needed to address external market demands as well as in building internal capabilities.